2017
DOI: 10.3892/mco.2017.1394
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in patients with skeletal-related events at non-small-cell lung cancer diagnosis

Abstract: Abstract. The aim of the present study was to detect prognostic factors in patients with skeletal-related events (SREs) and bone metastasis at the time of non-small-cell lung cancer (NSCLC) diagnosis. A total of 85 NSCLC patients were retrospectively enrolled, 47 (55.2%) of whom presented with SREs at the time of NSCLC diagnosis. Multivariate logistic regression analysis identified squamous cell carcinoma as a risk factor for SRE. Kaplan-Meier analysis demonstrated that there was no difference in the overall s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The incidence of SREs in non-small-cell lung cancer ranges from 40% to 65% [28], [29], [30], and it ranges from 8.5% to 63.5% in SCLC according to reported studies [12,[30], [31], [32], [33]] (see Table 7). In a study by Katakami N et al, the incidence of SREs in SCLC was lower than that in NSCLC, and the incidence of SREs in extensive small-cell lung cancer was only 8.5% [30].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of SREs in non-small-cell lung cancer ranges from 40% to 65% [28], [29], [30], and it ranges from 8.5% to 63.5% in SCLC according to reported studies [12,[30], [31], [32], [33]] (see Table 7). In a study by Katakami N et al, the incidence of SREs in SCLC was lower than that in NSCLC, and the incidence of SREs in extensive small-cell lung cancer was only 8.5% [30].…”
Section: Discussionmentioning
confidence: 99%
“…Da Silva et al, 11 in a retrospective series of 95 patients with a median follow-up of 4.4 months, found that the overall survival time was lower in patients who experienced SREs. In contrast, Tominaga et al, 12 in a study of 85 patients, of whom 47 presented with SREs, found no statistically significant difference in overall survival between the patients who experienced SREs and those who did not. In our study, the incidence rate of mortality was higher in patients who experienced an SRE; however, the overall survival time was not significantly different between the SRE and non-SRE cohorts (p = 0.43).…”
Section: Discussionmentioning
confidence: 86%
“…Today, patients with ABC are given a larger number of choices in treatment options, including new drugs (Eribulin), endocrine treatment (Fulvestrant), molecular targeted therapies (Palbociclib, Pertuzumab) and small tyrosine-kinase inhibitors (Neratinib). As a result, the past nomogram may have underestimated the expected OS of patients treated with current chemotherapeutic and biological agents (20)(21)(22)(23). Therefore, the validations of the existing prediction models for ABC showed a modest result with poor c-statistics ranging from 0.50 to 0.63 (24).…”
Section: Discussionmentioning
confidence: 99%